Land Capability and Suitability Assessment for Sweet Potato (ipomoea batatas l.) in Cimanggung Sub District, Citarik Sub watershed, West Java - Rina Devnita; Marenda Ishak Sonjaya Sule; Cucu Suherman; Apong Sandrawati; Widara Almaghfirah Ismail (Soilrens, 2021)
Cimanggung Sub District, located in the area of Citarik Sub Watershed, West Java, Indonesia, is one of important watershed that support life and water need. However, the pollution in this sub watershed is high, degraded the environment. Therefore, the agricultural management must be suitable with land capabilty and land suitability. The objective of this resarch was to evaluate the land capability and suitability for sweet potato (Ipomoea batatas, L). The assessment used the limiting factor for land capability and matching table for land suitability. The results showed that the Cimanggung Sub District consisted of 13 land mapping unit (LMU) with land capability classes: II- L2,E1,R1, LMU 8; III-P4, LMU 10; IV- L3, KE6, LMU 1, 2, 4, 6, 9, 12 and 13; VI-L4, LMU 5 and 7; VII15, LMU 3 and11. Areas suitable for agriculture were classes II, III, and IV (LMU 8, 10, 1, 2, 4, 6, 9, 12 and 13) and the areas non suitable for agriculture were classes VI and VII (LMU 5, 7 and 3). The actual land suitability for Cilembu sweet potato was S3 at LMU 8 and 10 and N1 at LMU 1, 2, 4, 6, 9, 12, and 13 with the main limiting factors were nutrient retention and rooting zone. Liming is the management that can be used to improve potential land suitability to LMU 1, 2, 4, 6, 12 and 13, which improve Nnr to S3nr, and to LMU 8 and 10, improve S3nr to S2nr. Clay fraction limiting factor in LMU 9 was irreparable.